Avoiding a crisis of motivation for ocean management under global environmental change. (27th April 2017) - Mumby, Peter J.; Sanchirico, James N.; Broad, Kenneth; Beck, Michael W.; Tyedmers, Peter; Morikawa, Megan; Okey, Thomas A.; Crowder, Larry B.; Fulton, Elizabeth A.; Kelso, Denny; Kleypas, Joanie A.; Munch, Stephan B.; et al.
Abstract: Climate change and ocean acidification are altering marine ecosystems and, from a human perspective, creating both winners and losers. Human responses to these changes are complex, but may result in reduced government investments in regulation, resource management, monitoring and enforcement. Moreover, a lack of peoples' experience of climate change may drive some towards attributing the symptoms of climate change to more familiar causes such as management failure. Taken together, we anticipate that management could become weaker and less effective as climate change continues. Using diverse case studies, including the decline of coral reefs, coastal defences from flooding, shifting fish stocks and the emergence of new shipping opportunities in the Arctic, we argue that human interests are better served by increased investments in resource management. But greater government investment in management does not simply mean more of "business‐as‐usual." Management needs to become more flexible, better at anticipating and responding to surprise, and able to facilitate change where it is desirable. A range of technological, economic, communication and governance solutions exists to help transform management. While not all have been tested, judicious application of the most appropriate solutions should help humanity adapt to novel circumstances and seek opportunity where possible. Abstract : Using five diverse case studies, ranging from climate impacts on coral reefs to shifts in fisheries distributions to opening of the Arctic for shipping, we reveal the rational drivers that might generate reductions in management regardless of whether global change is providing benefits or costs to human society. We argue that better outcomes will follow from greater management investment. We then discuss the key challenges to make management more effective and flexible.